Mobile Technology as Part of Banks’ Business Model - Klimontowicz, Monika; Harasim, Janina (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
During the last few decades, the banking market has changed significantly making banks face new challenges. Mobile technology development has had a powerful impact on all human activities including banking. Mobile technology has changed both the information and communication sharing, as well as customers’ market behaviour. All these changes should be taken into account in the process of searching for competitive advantage factors and designing banks’ business models. The purpose of the paper is to propose the framework for banks’ business model that incorporates using mobile technology and creating a competitive advantage. The foundation of this framework is based on theoretical considerations. The paper analyses contemporary business models used by banks, their value proposals and their relation to customers’ needs and expectations. The research highlights the routes for using mobile technology in the further development of banks’ business models from the perspective of the process of creating and delivering value for customers.